Types and concentration affect of natural preservatives on the quality of palm sugar - Naufalin, Rifda Naufalin; Yanto, Tri; Sulistyaningrum, Anna (Jurnal Teknologi Pertanian, 2013)
Coconut sap easily damaged, so the need for the preservation process. Farmers usually use (laru) was added a solution of lime with mangosteenrind and jackfruit wood chips to conserve juice. But the availability of a preservative is limited so that not a few farmers who use synthetic preservatives, sodium metabisulfite. Some natural preservatives that can be used as an alternative to extend the shelf life of coconut sap are betel leaves, clove leaf, guava leaves, wooden cup, and tea leaves. These materials have bioactive components that can act as antimicrobia.This research aims to 1) determine the effect of the type of natural preservatives to maintain freshness of coconut sap and quality of coconut sugar, 2) determine the effect of concentration of natural preservatives to maintain freshness of coconut sap and quality of coconut sugar, 3) determine the effect of the old store on the quality of coconut sap , 4) determine the effect of combined treatment of natural preservative type and concentration of preservatives on the quality of the coconut sugar.The research consisted of two phases. The results of phase 1 showed that the coconut sap is added preservative clove leaves (M4), guava leaves (M5) and mangosteenrind (M1) with concentration of 4.5% (K1) gave pH value, levels of sucrose and the highest sensory when compared with other preservatives. The results of phase 2 showed that coconut sugar is added to the preservative mangosteen rind, clove leaf, and guava leaves not significant difference to the chemical variables (water content, ash content, reducing sugar content, and total sugar content), but gave significant influence to organoleptic variables (color, aroma, flavor, texture, and preferences)..